La trayectoria del zoólogo José Yepes: colecciones, viajes y zoogeografía en las décadas de 1930 y 1940 - García, Susana Valeria (2018)
For almost fifteen years, José Yepes organized and increased the collection of mammals of the Argentine Museum of Natural Sciences of Buenos Aires. This zoologist was mainly dedicated to the study of the argentine xenarthrans and rodents as well as to the promotion of zoogeography. He made observations and collections in several regions of western Argentina, predominantly in mountainous and hilly areas. He also participated in wildlife protection movements in the 1940s. This article relates some biographical information of this zoologist and some material and institutional aspects of his scientific practices.